AC-WC Mixed Characterstics With Temperature Version of Mixing - Rainal, Rainal; Pratomo, Priyo; Sulistiyorini, Rahayu (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
This study was conducted to determine the effect of temperature variations on the mixing processof the hot mix asphalt (hot mix asphalt) to Marshall parameters with reference to the specificationof Bina Marga, 2010.Variations in mixing temperature 125 o C, 135 o C, 145 o C, 155 o C, 160 o C AC-WC layer smoothgradations center limit with asphalt content of 5.7%, at a mixing temperature of 125 oC does notmeet the Bina Marga specifications, because the value of the air voids in the mix (VIM) at atemperature of 125 o C at 5.611%, which exceeds the minimum standards at 3.5% to 5%. As for thetemperature variation of 135 o C to 160 o C mixing has met the minimum value of the Marshallparameter. Next to the mixing temperature variations upper limit 6.8% asphalt contenttemperatures are not eligible to be in a temperature of 125 o C. Due to a temperature of 125 o Cvalue of the cavity filled with asphalt (VFA) of 62.718% below the minimum standard value that isequal to 65%. As for the value of air voids in the mix (VIM) which exceeds the minimum value of5% is in the temperature 125 o C, 135 o C, 145 o C which each value by 7.778%, 6.8919%, 6.2490%,and then at a temperature of 160 o C for 3 , 1429% of the value below the minimum value of 3.5%.Only at a temperature of 155 o C which meet Marshall parameter values.Keywords : Temperature, Asphalt Concrete-Wearing Course (AC-WC), Marshall Parameter ,BinaMarga Specification 2010.